(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
Crisis management is a crucial aspect of school administration, as unforeseen disruptions can significantly impact educational institutions. Effective crisis management ensures continuity of operations, safety of students and staff, and preservation of institutional integrity. This paper explores strategies for effective crisis management in school administration, emphasizing the importance of preparedness, communication, and collaboration. By implementing structured crisis plans, training staff, and fostering community partnerships, school leaders can better anticipate, mitigate, and recover from crises. This study also highlights the importance of post-crisis evaluation and the role of leadership in navigating educational challenges.